1985
DOI: 10.1128/iai.50.1.1-8.1985
|View full text |Cite
|
Sign up to set email alerts
|

Gamma interferon activates human macrophages to become tumoricidal and leishmanicidal but enhances replication of macrophage-associated mycobacteria

Abstract: Recombinant human gamma interferon (rIFN-y) was examined for its ability to activate human peripheral blood monocyte-derived macrophages to kill tumor cells and to affect the replication of two phylogenetically distinct intracellular pathogens, Mycobacterium tuberculosis and Leishmania donovani. Macrophages preincubated overnight with doses of rIFN-y from 5 to 500 U/ml killed [3H]thymidine-labeled mouse L929 tumor targets, as measured by the release of [3H]thymidine into the supernatant after 48 h. Counts of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
2

Year Published

1988
1988
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(90 citation statements)
references
References 35 publications
7
81
2
Order By: Relevance
“…Although their effectiveness in blocking the relevant cytokines had not been tested directly, the lack of a significant effect of the neutralizing antibodies on the growth of M. tuberculosis confirms a previous finding using a model of M. tuberculosis-infected macrophages [16]. Previous studies performed by several groups to delineate the effect of cytokines on the growth of M. tuberculosis in human macrophages in vitro have shown controversial results [14][15][16]20,22]. Some of these studies have shown only weak inhibition [20,22], whereas others have shown enhancement [15,22] of the growth of virulent M. tuberculosis in human monocytes/macrophages activated with IFNγ.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although their effectiveness in blocking the relevant cytokines had not been tested directly, the lack of a significant effect of the neutralizing antibodies on the growth of M. tuberculosis confirms a previous finding using a model of M. tuberculosis-infected macrophages [16]. Previous studies performed by several groups to delineate the effect of cytokines on the growth of M. tuberculosis in human macrophages in vitro have shown controversial results [14][15][16]20,22]. Some of these studies have shown only weak inhibition [20,22], whereas others have shown enhancement [15,22] of the growth of virulent M. tuberculosis in human monocytes/macrophages activated with IFNγ.…”
Section: Discussionsupporting
confidence: 60%
“…Several cytokines have been suggested previously to have an inhibitory or enhancing effect on the growth of M. tuberculosis in human macrophages [15][16][17][18][19][20][21][22][23][24][25]. Among these, TNFα and IFN-γ have been studied extensively [15][16][17][18][19][20][21][22][23][24][25]. In the present work, to study the effect of TNF-α, IFN-γ, IL-12 and IL-10 on M. tuberculosis growth in whole blood cultures, we have used two approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Although Fe is required for M.tb growth, it was not clear whether the decrease in Fe acquisition by M.tb located in HFE -MDM was sufficient to alter bacterial growth in the macrophage. In spite of decreasing access of M.tb to Fe, previous studies found that IFN-␥ treatment of human MDM does not inhibit the in vitro growth of M.tb [34,43]. Therefore, we compared growth of intracellular M.tb over time in MDM from hemochromatosis and healthy control subjects.…”
Section: Mtb Growth Is Decreased In Macrophages From Hemochromatosismentioning
confidence: 96%
“…Whereas the antimycobacterial properties of murine peritoneal macrophages are strongly activated by natural and E. co//-derived IFN-y [14], the situation is less clear in man. Indeed, recent papers have demonstrated that human macrophages can become activated by gamma interferon in their tumoricidal and Leishmaniacidal properties, but that macrophage treatment with the lymphokine has weak, variable, or even enhancing effects on Myeobacterium tuberculosis replication [6,14].…”
Section: Kris Huygen Instituut Pasteur Van Brabant 642 Engelandstramentioning
confidence: 99%